Differences in amino acid frequency in CagA and VacA sequences of Helicobacter pylori distinguish gastric cancer from gastric MALT lymphoma. Issue 1 (December 2016) - Hashinaga, Masahiko; Suzuki, Rumiko; Akada, Junko; Matsumoto, Takashi; Kido, Yasutoshi; Okimoto, Tadayoshi; Kodama, Masaaki; Murakami, Kazunari; Yamaoka, Yoshio
Abstract Background Helicobacter pylori is a pathogenic bacterium that causes various gastrointestinal diseases. The most common gastric malignancies associated withH. pylori are gastric cancer and lymphoma of mucosa associated lymphoid tissue (MALT).Helicobacter pylori virulence genes, namelycagA andvacA, are known to be associated with malignancy development. Conventionally, cagA andvacA were classified by looking at partial sequences of the genes. However, such genotyping has hardly proven useful predicting different risks for gastric cancer or MALT lymphoma. In search of new loci that distinguish these diseases, we investigated the full sequences ofcagA andvacA . Results We comparedcagA andvacA sequences of 18 and 12H. pylori strains obtained, respectively, from patients with gastric cancer and MALT lymphoma in Oita, Japan. Conventional genotyping ofcagA andvacA showed no significant difference between the two diseases. We further investigated the full protein sequences of CagA and VacA to identify loci where allele frequency was significantly different between the diseases. We found four such loci on CagA, and three such loci on VacA. We also inspected the corresponding loci on the genes of 22 gastritis strains that potentially lead to gastric cancer or MALT lymphoma in the long run. Significant differences were observed at one CagA locus between gastritis and MALT lymphoma strains, and at one VacA locus between gastritis and gastric cancer strains. Conclusions We found novel candidate loci inH. pylori virulence genes in association with two different types of gastric malignancies that could not be differentiated by conventional genotyping. Biological connotations of the amino acid polymorphisms merit further study.